(untitled) (Acta Theologica, 2022)
This article is an exposition of Rian Venter’s Trinitarian theology from the perspective of an appreciation of his intellectual and theological accomplishments, with specific focus on his discussion of space and time concerning the Trinity. In the first part of this article, I give a brief overview of the main themes of Venter’s theology to highlight the main Trinitarian questions with which he engages. In the second part, I focus on Venter’s specific work on “space and the Trinity”, which he creatively specifically explored in his 2006 article, “Space, Trinity and city: A theological exploration”. In the final part of the article, I engage more critically with Venter’s work on the theme “time, space and the Trinity”, where I juxtapose his work with that of Robert Jenson. I conclude that Venter’s Trinitarian theology contributed immensely to enriching theological thinking on aspects such as space and ethics. Still, the focus on the relation between the Trinity and time could be explored in more detail, while his emphasis on the transcendent nature of the Trinity created some unresolved metaphysical challenges.